Learning Retention of Preservice Science Teachers About the Nature of Science: an Explicit Reflective Inquiry-Based Learning and History of Scientist - Safkolam, Roswanna; Sofilan Madahae; Phurkonni Saleah (Jurnal Pendidikan IPA Indonesia, 2024)
Understanding the nature of science is one component of knowing science and is key for science teacher students to to have a correct understanding. Therefore, the researcher was interested in studying the learning persistence of understanding the nature of science among the science teacher students after the course with a series of inquiry-based learning activities combined with reflective indication and history of scientists for 1 month using a combination of research methodology. The target group for the research was 35 science teacher students of a Rajabhat University in southern Thailand. The research tools include 1)learning management plan 2) Questionnaire on understanding the nature of science 3) a semi-structured interview form on understanding the nature of science. For quantitative data analysis with percentage, mean, standard deviation, t-test for dependent sample, and analyze qualitative data with content-oriented analysis. The results showed that: Science teacher students who studied with the learning activity set had a statistically significant average score of understanding the nature of science after a one-month learning gap, not statistically significantly different from after the course, at a level of .05.All scientific community resolutions feature the nature of science. The results show that incorporating the inquiry process into teaching, along with an explicit reflective approach and the historical context of scientists, can greatly enhance the student's understanding and learning retention of the nature of science.